Adjustment in the textile and clothing industry: The case of West Germany - Axel Dietmar Neu (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1973)
Among the industries expected in future to be - according to several surveys - exposed to high pressure through adjustment: requirements due to accelerating export performance by developing countries, the textile and clothing industry occupies a predominant rank. The question whether developing countries are well advised to penetrate into the markets of developed countries as new suppliers of textile and clothing products has subsequently led to vehement controversies. The following contribution does not intend to examine more closely the questions raised in this connection, but, within the limits of this contribution, the following aspects shall be treated: - extent and direction of the structural change in the textile and clothing industry of the Federal Republic of Germany during the last decade, and their origin; - to show the protective measures granted to the West German producers of textile and clothing goods vis-a-vis their competitors from so - called low price countries and to analyse the quantitative, effects of these protective measures; - to examine the question which percentage of the imports from so-called low price countries is absorbed by the different industrial countries and whether it is possible to develop standards for a fair distribution of the import burden from low price countries; - finally to analyse more closely the development of textile and clothing exports from developing and so-called low price countries, in order to obtain possibly data about the future development.
Keywords: 330